European Perspectives on the Common European Sales Law - Plaza Penadés, Javier; Martínez Velencoso, Luz M. (Studies in European Economic Law and Regulation,, 2015)
This book presents a complete and coherent view of the subject of Common European Sales Law from a range of European perspectives. The book offers a comparison of the CESL with the CISG, as well as pre-existing instruments, including the Draft Common Frame of Reference (DCFR) and the Principles of European Contract Law (PECL). It analyses the process of enactment of CESL and its scope of application, covering areas such as the sale of goods, the supplying (licensing) of digital content, the supply of trade-related services, and consumer protection. It examines the design of the CESL bifurcating businesses into large and small-to-medium sized enterprises, and the providing of rules covering digital content and the supply of trade-related services. Lastly, it studies the field of application of the CESL combined with the already existing EU consumer protection laws, as well as nation-specific laws.